Associations of exposure to intimate partner violence and parent-to-child aggression with child competence and psychopathology symptoms in two generations. (May 2020) - Capaldi, Deborah M.; Tiberio, Stacey S.; Shortt, Joann Wu; Low, Sabina; Owen, Lee D.
Abstract: Background: Associations of exposure to intimate partner violence (IPV) and parent-to-child aggression (PCA) with child adjustment have not been examined adequately for community samples. Objective: To examine main, cumulative, and interactive associations of IPV and PCA (separately for physical and psychological aggression) with four aspects of child adjustment (i.e., externalizing and internalizing behavior; social and scholastic competence). Associations were examined between (a) G1 parent behavior and the adjustment of G2 boys ( N = 203) at ages 13–14 years and (b) G2 parent behavior and the adjustment of G3 children ( N = 294) at ages 4–5 and 11–12 years. Participants and setting: Families in a prospective, multigenerational dataset. Methods: Measures included reports by caregivers, children, and teachers. Cross-sectional regression models (controlling for parent socioeconomic status and G3 child gender) examined: (a) main effects of IPV or PCA, (b) the simultaneous (i.e., cumulative) effects of both IPV and PCA, and (c) interactive effects of IPV and PCA (sample size permitting) on each of the child adjustment outcomes. Results: When considered simultaneously, PCA (but not IPV) was associated with each aspect of child adjustment. The interaction between PCA and IPV indicated lower G2 adolescent scholastic competence and greater G3 preschool externalizing behavior for children exposed to lower levels of IPV and higher levels of PCA. Conclusion: Psychological and physical PCA were associated with child adjustment problems even when accounting for IPV. Findings support the use of evidence-based programs to prevent PCA and PCA-associated child adjustment problems.